The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2196/19623
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint Biometric System Hygiene and the Risk of COVID-19 Transmission

Abstract: Biometric systems use scanners to verify the identity of human beings by measuring the patterns of their behavioral or physiological characteristics. Some biometric systems are contactless and do not require direct touch to perform these measurements; others, such as fingerprint verification systems, require the user to make direct physical contact with the scanner for a specified duration for the biometric pattern of the user to be properly read and measured. This may increase the possibility of contamination… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 104 publications
0
14
0
2
Order By: Relevance
“…Both medical images and doctor-patient dialogue are tools for physicians to know their patients. For patients with a certain type of disease, their disease characteristics are statistical characteristics [44] , [45] , [46] . For example, as shown in Fig.…”
Section: Multi-modal Covid-19 Pneumonia Datasetmentioning
confidence: 99%
“…Both medical images and doctor-patient dialogue are tools for physicians to know their patients. For patients with a certain type of disease, their disease characteristics are statistical characteristics [44] , [45] , [46] . For example, as shown in Fig.…”
Section: Multi-modal Covid-19 Pneumonia Datasetmentioning
confidence: 99%
“…Damer et al [7] study the effect of wearing face mask on face recognition systems and found significant drop in recognition accuracy when subject is wearing face mask. Finger print authentication can be a solution but it requires to touch the surface of the scanner which may increase the possibility of contamination and spread of any infectious diseases [18]. Hence in this critical scenario of COVID 19, this solution cannot be acceptable when every automated system needs to work on contact less approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Especially in multi-user applications, hygienic concerns lower the acceptability of contact-based fingerprint systems and hence limit their deployment. In a comprehensive study, Okereafor et al [ 1 ] analyzed the risk of an infection by contact-based fingerprint recognition schemes and the hygienic concerns of their users. The authors concluded that contact-based fingerprint recognition carries a high risk of an infection if a previous user has contaminated the capturing device surface, e.g., with the SARS-CoV-2 virus.…”
Section: Introductionmentioning
confidence: 99%